Ang gusto kong pamilya a creative solution to the resistance of urban poor families in metropolitan manila to family planning - Valdon, Nielle Angela Blancaflor; Tañedo, Jose Alberto (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Overpopulation is one of the many pressing issues of the country. One of the main solutions to the matter is family planning. Since the 1960s, there had been many campaigns and promotions conducted by government and non-government institutions to deliver the message to the Filipino people. Today, despite of the many advances in contraceptive technology, the population of the country still grows. Taking Metropolitan Manila, Philippines as a sample correspondent, findings made reflect that urban poor Filipinos have an unmet need for family planning - while most of them are unaware of what family planning is, data suggest that they have a wrong perception on the matter. The creative campaign, hence, will provide a communication that will seek to address the concerns of the target audience by referencing their values, beliefs, and point-on-view.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 34-35.
Keywords: Family planning; Overpopulation